The deadly politics of giving : exchange and violence at Ajacan, Roanoke, and Jamestown - Mallios, Seth, 1971- (University of Alabama Press, 2006)
A clash of cultures on the North American continent. With a focus on indigenous cultural systems and agency theory, this volume analyzes Contact Period relations between North American Middle Atlantic Algonquian Indians and the Spanish Jesuits at Ajacan (1570-72) and English settlers at Roanoke Island (1584-90) and Jamestown Island (1607-12). It is an anthropological and ethnohistorical study of how European violations of Algonquian gift-exchange systems led to intercultural strife during the late 1500s and early 1600s, destroying Ajacan and Roanoke, and nearly destroying Jamestown.